INTEGRATED PORT ENVIRONMENTAL PROCESS MATURITY MODEL – THEORETICAL FRAMEWORK - Charłampowicz, Jędrzej (Scientific Journal of Gdynia Maritime University, 2026)
This paper introduces the Integrated Port Environmental Process Maturity Model (IPEPMM), a theoretical framework aligning environmental process maturity with measurable performance outcomes in maritime ports. The model synthesizes two previously independent approaches: the Environmental Process Maturity (EPM) ladder, which structures environmental capability development, and the Port Environmental Index (PEI), which quantifies environmental outcomes through standardized indicators. By embedding IoT-enabled data governance and stakeholder legitimization into one cohesive system, IPEPMM bridges the gap between process- -based maturity and evidence-based performance. The framework redefines maturity stages as verifiable managerial commitments, linking capability progression to quantitative environmental improvements. This conceptual integration offers both theoretical advancement and practical guidance for achieving accountable, data-driven environmental management in smart ports while outlining directions for empirical validation and model refinement.